2019
DOI: 10.3389/fpsyg.2019.00037
|View full text |Cite|
|
Sign up to set email alerts
|

The (Not So) Changing Man: Dynamic Gender Stereotypes in Sweden

Abstract: According to Social Role Theory, gender stereotypes are dynamic constructs influenced by actual and perceived changes in what roles women and men occupy (Wood and Eagly, 2011). Sweden is ranked as one of the most egalitarian countries in the world, with a strong national equality discourse and a relatively high number of men engaging in traditionally communal roles such as parenting and domestic tasks. This would imply a perceived change toward higher communion among men. Therefore, we investigated the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
3
49
1
1
Order By: Relevance
“…In line with social role theory's predictions, studies conducted in Western, more economically developed nations (i.e., Germany, Spain, Sweden, and the United States) as well as non‐Western, less developed nations (i.e., Brazil, Chile, and Ghana; Bosak, Eagly et al., 2018; Gustafsson Sendén et al., 2019) showed that perceived changes in women's occupational roles were associated with greater ascriptions of agentic traits to women (a similar argument is discussed by Kim et al., 2020). As men have not moved into communal social roles to the same extent that women have moved into agentic social roles (e.g., England, 2010), stereotypes of men have not changed to the same extent as stereotypes of women have; that is, in most nations men have not been associated with more communal traits over time (Diekman et al., 2005; Eagly et al., 2019; Gustafsson Sendén et al., 2019; Koenig & Eagly, 2014; Twenge, 1997, but see Haines et al., 2016 showing stereotype maintenance in the United States, and Bosak, Eagly et al., 2018 showing that men are increasingly associated with communion in Ghana). Thus, there is some evidence suggesting that in support of social role theory the extent of societal and economic changes facilitating men and women's equal participation across different social roles may be associated with the strength of individuals’ gender stereotypes.…”
Section: The Relationship Between Occupational Gender Segregation Andmentioning
confidence: 66%
See 1 more Smart Citation
“…In line with social role theory's predictions, studies conducted in Western, more economically developed nations (i.e., Germany, Spain, Sweden, and the United States) as well as non‐Western, less developed nations (i.e., Brazil, Chile, and Ghana; Bosak, Eagly et al., 2018; Gustafsson Sendén et al., 2019) showed that perceived changes in women's occupational roles were associated with greater ascriptions of agentic traits to women (a similar argument is discussed by Kim et al., 2020). As men have not moved into communal social roles to the same extent that women have moved into agentic social roles (e.g., England, 2010), stereotypes of men have not changed to the same extent as stereotypes of women have; that is, in most nations men have not been associated with more communal traits over time (Diekman et al., 2005; Eagly et al., 2019; Gustafsson Sendén et al., 2019; Koenig & Eagly, 2014; Twenge, 1997, but see Haines et al., 2016 showing stereotype maintenance in the United States, and Bosak, Eagly et al., 2018 showing that men are increasingly associated with communion in Ghana). Thus, there is some evidence suggesting that in support of social role theory the extent of societal and economic changes facilitating men and women's equal participation across different social roles may be associated with the strength of individuals’ gender stereotypes.…”
Section: The Relationship Between Occupational Gender Segregation Andmentioning
confidence: 66%
“…Social role theory posits that situational factors such as the economy, social structure, culture, and ecology play a role in shaping occupational gender segregation and the variability in occupational gender stereotypes between societies (e.g., Eagly & Wood, 2012). However, social role theory has predominantly been investigated in Western societies, such as the United States and Europe (e.g., Bosak et al., 2012; Cejka & Eagly, 1999; Gustafsson Sendén et al., 2019; Koenig & Eagly, 2014, but see Bosak, Eagly et al., 2018). Research systematically investigating social role theory's predictions about occupational gender segregation and gender stereotypes in different national contexts is limited.…”
Section: The Relationship Between Occupational Gender Segregation Andmentioning
confidence: 99%
“…This was surprising since competence has been strongly associated with masculinity (Fiske et al, 2007). However, recent research show that competence is one aspect of gender stereotypes that has changed the most over the years, and that women now sometimes are perceived as more competent than men (Gustafsson Sendén et al, 2019;Eagly et al, 2020). Hence, the results are not contradicting of recent research.…”
Section: Resultsmentioning
confidence: 85%
“…Hence, agentic traits are traditionally associated with masculinity, while communal traits are traditionally associated with femininity. Importantly, gender stereotypes function both prescriptively (what women and men should engage in, and how they should be), and proscriptively (what they should not engage in and be) (Gustafsson Sendén et al, 2019;Hentschel et al, 2019).…”
Section: Gender Stereotypesmentioning
confidence: 99%
“…Sweden is also known for its strong norms of gender equality, including gender-egalitarian ideas of care responsibilities. Research has indicated that there has not been substantial changes in policies about eldercare (for overview, see Peterson 2017;Meagher and Szebehely 2019) or norms of gender equality during the last decade (Nyman et al 2018;Gustafsson Sendén et al 2019).…”
Section: Introductionmentioning
confidence: 99%